Nondestructive testing based weld defect classification using tetrolet transform - Kalaiselvi, V.; John Aravindhar, D. (International Journal of Engineering and Technology, 2018)
The process of visual inspection of weld elements is an important task for providing a safe and reliable outsource in most of the industrial sectors. As most of the industries are still using only the human vision process of manually operation that makes the test results look more subjective. Due to this an image processing algorithm based on the Non-Destructive Testing (NDT) method is introduced to test the welding surface for recognizing the external and internal flaws without disturbing its suitability for service. The proposed system is implemented by using the GD X-ray weld image database. Due to less number of input images, the sub images are extracted and are separated as the normal and the defected images and are used as training and testing set of input images. Then the tetrolet transform is applied for both the testing and training process in order to obtain the maximum coefficients from which the features like energy and entropy features are extracted. Then the testing can be done by using the Support Vector Machines (SVM) classifier for the classification purpose and are validated using the k-fold algorithm. Result shows that the proposed system produces promising results with 100% of classification accuracyÂ